Stress fracture of the first rib in a hockey goalie - Cross, E. R.; Seligman, E. S.; Corrado, G. D. (The Journal of Sports Medicine and Physical Fitness, 2024)
First rib stress fractures are uncommon in athletes and diagnosis requires a high degree of clinical suspicion. Diagnostic delay may increase risk of poor healing and long-term complications. Case reports and series describe these injuries primarily in overhead athletes; proposed contributing factors include anatomic susceptibility to stress and repetitive opposing muscular forces. We describe an ice hockey goalie with acute-on-chronic thoracic back pain who was found to have a first rib stress fracture, which to our knowledge is the first reported in this sport. We hypothesize that biomechanical stress from new stick positioning contributed to the injury. Our patient recovered symptomatically with conservative treatment; however, imaging suggested nonunion of the fracture site and possible pseudoarthrosis.